Enhancement of Tc in the atomic phase of iodine-doped hydrogen at high pressures. Issue 48 (19th November 2015) - Duan, Defang; Tian, Fubo; Liu, Yunxian; Huang, Xiaoli; Li, Da; Yu, Hongyu; Ma, Yanbin; Liu, Bingbing; Cui, Tian
Abstract : H2 molecular units dissociate and form a novel atomic phase with R 3̄ m . Abstract : The high-pressure structures and superconductivity of iodine-doped hydrogen have been studied by ab initio calculations. Above 100 GPa, we discover a stable phase with Pnma symmetry in the H2 I stoichiometry that consists of a monatomic iodine tube trapping hydrogen molecular units. Interestingly, H2 molecular units dissociate and form a novel atomic phase with R 3̄ m symmetry at 246 GPa. Further electron–phonon coupling calculations predict the critical temperature of superconductivity T c to be 3.8 K for the Pnma phase and 33 K for the R 3̄ m phase at 240 GPa. Significantly, the T c of the R 3̄ m phase is enhanced approximately 8 times that of the Pnma phase, which is mainly attributed to the reason that H2 molecules are broken exhibiting an atomic character in the R 3̄ m phase.